2014
DOI: 10.1158/1078-0432.ccr-14-0305
|View full text |Cite
|
Sign up to set email alerts
|

miR-409-3p/-5p Promotes Tumorigenesis, Epithelial-to-Mesenchymal Transition, and Bone Metastasis of Human Prostate Cancer

Abstract: Purpose miR-409-3p/-5p is a microRNA expressed by embryonic stem cells and its role in cancer biology and metastasis is unknown. Our pilot studies demonstrated elevated miR-409-3p/-5p expression in human prostate cancer bone metastatic cell lines, therefore we defined the biological impact of manipulation of miR-409-3p/-5p in prostate cancer progression and correlated the levels of its expression with clinical human prostate cancer bone metastatic specimens. Experimental Design miRNA profiling of prostate ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 34 publications
(40 reference statements)
2
105
1
Order By: Relevance
“…c-myc promotes the initiation of GC (24) and in the present study, it was demonstrated that SH2B1 overexpression significantly promotes c-myc expression in normal gastric epithelial cells. Furthermore, it has been demonstrated that the EMT serves an important function in tumorigenesis (25,26) and the present study indicated that SH2B1 overexpression significantly promotes the EMT.…”
Section: Discussionsupporting
confidence: 63%
“…c-myc promotes the initiation of GC (24) and in the present study, it was demonstrated that SH2B1 overexpression significantly promotes c-myc expression in normal gastric epithelial cells. Furthermore, it has been demonstrated that the EMT serves an important function in tumorigenesis (25,26) and the present study indicated that SH2B1 overexpression significantly promotes the EMT.…”
Section: Discussionsupporting
confidence: 63%
“…miRNAs are endogenous, single-stranded, non-coding RNAs which are approximately 22 nucleotides in length and may suppress the post-transcriptional expression of target genes and are consequently involved in the regulation of various cellular processes, e.g., cell apoptosis, differentiation, development and metastasis (9,18,19). Growing evidence has reinforced the fact that miRNAs are frequently deregulated and aberrantly expressed in certain types of cancer, by acting as either tumor suppressors (9,20) or oncogenes (21, 22), and that they play a central role in carcinogenesis. Among these miRNAs, miR-214 has attracted increasing attention due to its critical role in the development of different types of cancer (8,10); however, accumulating evidence has confirmed that miR-214 exerts various, even inverse, effects in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that miRNAs may function as a novel class of both oncogenes and tumor suppressors (Calin and Croce 2006;Xu et al 2012;Wei et al 2012;Hou et al 2011;Josson et al 2014). Aberrant expression of miRNA signatures has been demonstrated in prostate tumor samples and has been detected in serum of men with PCa Hao et al 2011;Huo et al 2014 cells and found that overexpressed miR-345 suppressed the growth of LNCaP and PC-3M cells, induced prostate cancer cell apoptosis and promoted G1 phase arrest.…”
Section: Discussionmentioning
confidence: 99%